Housing Estate for Sustainable Social, Economic and Environment Development - Bahagia Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; Muhammad Shiddiq Ilham Noor; Zakky Muhammad Noor (Universitas Pahlawan Tuanku Tambusai, 2022)
Residential areas are growing rapidly in big cities. The purpose of this study is to find social, cultural and economic values in residential areas. The research method used is descriptive qualitative method. Meanwhile, the research sample used purposive sampling technique. Data was collected by means of in-dept-interview, documentation and observation. The results of the study indicate that social life, such as the establishment of social relations between residents, is associated with facilities such as mosques because mosques contain direct social values. Friendship is also built through religious activities such as tahlilan and at the playground. At the playground children can hone their social skills because they meet children who bring differences in terms of culture and religion. The advantage is that children can appreciate cultural and religious differences from an early age. Even hone togetherness because playing with toys requires other people. At the same time establishing friendship between mothers because when their children play in the garden, the mothers will supervise so that there is a greeting between mothers. Economically, traders may enter residential areas so that traders can profit economically. At the same time growing opportunities to become security officers and household assistants. Finally, there is environmental value because the playground is a green zone so that it can be used as a water catchment area and overcome flooding and reduce emissions.